Adaptability, Agility, and Readiness in Transformation Digital Learning Technology Post Pandemic - Amalia, Rahmatika Sari (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
This study aims to describe how adaptable, agile, and ready-for-change lecturers are when they use digital information-based learning technology before, during, and after the COVID-19 pandemic in higher education institutions in Indonesia. The pandemic has forced higher education institutions to use digital information-based learning technology to ensure continuity in the learning process. However, it is essential to assess whether this technology is still relevant and whether it will continue to be used after the pandemic ends. The using digital information-based learning technology depends on many factors such as adaptation, learning agility, and readiness for change. This study uses a literature review approach with the keywords utilization of digital information-based learning technology, COVID-19, readiness, adaptability, and learning agility. The results of this study indicate that the adaptability, learning agility, and readiness to change lecturers will determine whether they continue to use learning technology even after the pandemic. Based on these results, lecturers can improve their adaptability and learning agility, to be ready for changes by using renewable and up-to-date learning technology based on digital information technology. This will increase the quality and effectiveness of learning even after the pandemic ends.